1996
DOI: 10.1111/j.1365-2621.1996.tb13160.x
|View full text |Cite
|
Sign up to set email alerts
|

Pasteurization Efficiency of a HTST System for Human Milk

Abstract: An economical, small scale heat processing device was studied for rapid and efficient pasteurization of human milk while preserving immunoglobulins A,G and M. Using a continuous flow HTST milk pasteurizer, human milk inoculated with E. coli (10 6 CFU/mL) or S. aureus (10 7 CFU/mL) was heated at 71ЊC at flow rates of 5.9, 12.3 and 18.9 mL/ min. All conditions completely inactivated both microorganisms and resulted in negative alkaline phosphatase activity indicating complete pasteurization. Heat processing of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
1
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 30 publications
6
27
1
1
Order By: Relevance
“…However, Dhar et al (1996) found a higher retention for human IgA than for IgG at 71 to 74ЊC, probably due to different experimental conditions. Resmini et al (1989a) obtained three immunoglobulin fractions from bovine milk by reversed-phase HPLC, from which they considered the IgG fraction as the more thermostable.…”
Section: Denaturation Of Immunoglobulinsmentioning
confidence: 50%
“…However, Dhar et al (1996) found a higher retention for human IgA than for IgG at 71 to 74ЊC, probably due to different experimental conditions. Resmini et al (1989a) obtained three immunoglobulin fractions from bovine milk by reversed-phase HPLC, from which they considered the IgG fraction as the more thermostable.…”
Section: Denaturation Of Immunoglobulinsmentioning
confidence: 50%
“…sIgAs represents the 363 majority of IgA in HM (Goldsmith et al, 1983). In early reports, the retention of sIgAs and /or the 364 total IgAs following HTST was found to be complete (Goldblum et al, 1984), decreased with 365 respect to raw milk (about 60% for Dhar et al, 1996) and equal to that of HoP with respect to raw 366 milk (63% according to Goldsmith et al, 1983 pasteurization (Mayayo et al, 2016). In all these reports, lysozyme activity was determined using a 378…”
Section: Discussion 325mentioning
confidence: 99%
“…Flash-heat is similar to the commercial HTST methods, which heat to 72°C for 15 seconds and have been shown to effectively kill bacteria and cytomegalovirus yet have limited impact on vitamins, lactoferrin, and IgA. Thus, HTST is viewed as the preferable heating technique for human milk 18,24,25. Pilot data also suggest that nutritional properties are retained after flash-heat in breastmilk collected from healthy mothers in the United States 26.…”
Section: Introductionmentioning
confidence: 99%